Membrane lipids and cell signaling. Issue 5 (October 2017) - Sunshine, Hannah; Iruela-Arispe, Maria Luisa
Abstract : Purpose of review: Reception and transmission of signals across the plasma membrane has been a function generally attributed to transmembrane proteins. In the last 3 years, however, a growing number of reports have further acknowledged important contributions played by membrane lipids in the process of signal transduction. Recent findings: In particular, the constituency of membrane lipids can regulate how proteins with SH2 domains and molecules like K-Ras expose their catalytic domains to the cytosol and interact with effectors and second messengers. Recent reports have also shown that the degree of saturation of phospholipids can reduce the activation of certain G-protein-coupled receptors, and signaling downstream to Toll-like receptor 4 with consequences to nuclear factor kappa B activation and inflammation. Levels of specific gangliosides in the membrane were reported to activate integrins in a cell-autonomous manner affecting tumor cell migration. Furthermore, high resolution of the association of cholesterol with the smoothened receptor has clarified its participation in sonic hedgehog signaling. These are some of the key advancements that have further propelled our understanding of the broad versatile contributions of membrane lipids in signal transduction. Summary: As we gain definitive detail regarding the impact of lipid–protein interactions and their consequences to cell function, the options for therapeutic targeting expand with the possibility of greater specificity.